Множинність осіб у деліктних зобов'язаннях за участю неповнолітніх осіб - Чернілевська, О. І.; Чернилевская, О. И.; Chernilevskaja, O. (Одеса : Юрид. л-ра, 2014)
Article is devoted to plurality of persons in delicts in which a minor participates. On the basis of analyzed court decisions in cases about compensating damage, being caused by a minor, the author pays attention to conditions of responsibility as well as features of mentioned damage compensation. In addition, the arguments about absence of subsidiary plurality of persons in delicts, being caused by a minor, are highlighted.
Чернілевська О. І. Множинність осіб у деліктних зобов'язаннях за участю неповнолітніх осіб / О. І. Чернілевська // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 268-274.
Keywords: множинність осіб; деліктне зобов’язання; неповнолітня особа; відшкодування шкоди; множественность лиц; деликтное обязательство; несовершеннолетний; возмещение вреда; plurality of persons; delict; minor; compensation of damage